Enhancing Paddy Yield in Kole Wetlands: Padasekharam Level Classification and Intervention Strategies - Sunil V G; Asish Benny; Chinchu V S; Aswathi Krishna R; Joyal Mathew; Sathyajith K S (Archives of Current Research International, 2025)
The Kole Wetlands of Kerala, a Ramsar-designated agroecosystem, play a vital role in regional food security, climate regulation, and rural livelihoods. This study presents a novel padasekharam-level classification model that integrates five-year productivity data (2019–2023), cultivated area, and inter-annual yield stability (Coefficient of Variation, CV) to identify heterogeneity across 271 management units. Padasekharams were grouped into eight typologies (A–H) using a three-dimensional framework: size (large/small), yield level (high/low), and yield stability (stable/unstable; CV threshold: 20%). Results revealed stark contrasts: Groups A (Large–High–Stable) and E (Small–High–Stable) demonstrated consistent performance due to robust infrastructure and climate-smart practices, while Groups D (Large–Low–Unstable) and H (Small–Low–Unstable) suffered from high volatility (CV >75%), driven by bund degradation, drainage congestion, and agronomic lapses. A group-specific intervention matrix linked field performance to tailored strategies, emphasizing water infrastructure rehabilitation (e.g., sluice installation for Group H), risk mitigation (e.g., submergence-tolerant varieties for Group F), and precision agronomy (e.g., site-specific nutrient scheduling and Alternate Wetting and Drying for Group A). Beyond the Kole, the model has applicability for similar floodplain rice ecosystems in Kuttanad (India), the Haor basins (Bangladesh), and the Mekong Delta (Vietnam). By linking yield classification with actionable strategies, this framework shifts policy emphasis from blanket subsidies toward localized, climate-smart investments. The approach supports Kerala’s Climate-Resilient Agriculture Mission and contributes to Sustainable Development Goal 2 (Zero Hunger).